The Implementation of "Qaulan Layyina" (QS. Taha: 44) by Preachers in the Q&A Program on Metro TV - Qori Hajidah Arianti; Rahmi; Yudha; Wildan; Luluk Fikri (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2025)
This study examines the implementation of the principle of qaulan layyina as mentioned in the Qur’an (QS. Taha: 44) within the context of Islamic preaching on Indonesian television, specifically in the Q&A program aired on Metro TV. Utilizing a descriptive qualitative approach supported by literature analysis, this research explores how preachers deliver religious messages with gentleness, empathy, and persuasion to a heterogeneous audience. The study highlights that the application of qaulan layyina is influenced by several factors, including the preacher’s personal understanding of Islamic ethical principles, their communication skills, and the structure of the television program. The findings demonstrate that most preachers succeed in maintaining a soft and inclusive tone, especially when responding to sensitive or controversial questions. Through this approach, they are able to minimize conflict, promote mutual respect, and uphold the core values of Islamic communication. This research contributes to the broader field of Islamic communication studies and offers practical insights for da’wah practices in modern media environments. Keywords: Qaulan Layyina, Da’wah, Q&A Di Metro TV.